Analisis Penyimpangan Prinsip Kerjasama dalam Percakapan Film "Laskar Pelangi" Karya Andre Hirata dan Implementasinya sebagai Materi Ajar Kesantunan Berbahasa Siswa SMP Negeri 1 Kartasura - Darnita, Devi, Prof.Dr. Markamah, M. Hum (2016)
The purpose of this study was to describe: (1) describe the forms of deviation principle of cooperation in the film conversation "Lakar Rainbow" by Andre Hirata; (2) describes the implementation of use conversation in the film Laskar Pelangi by Andre Hirata as teaching materials politeness students of SMP Negeri 1 Kartasura. This study used descriptive qualitative method. The data source of this research is the film script by Andre Hirata Laskar Pelangi. The data in this study a conversation or dialogue in the form of words, phrases, clauses, and sentences that contain a violation of the principle of cooperation in conversation film Laskar Pelangi by Andre Hirata. This research data collection techniques using the technique refer to obtain data done by listening to language use. Technical analysis of the data using a unified method pragmatic. The findings of this study indicate that: (1) The deviation of the principle of cooperation in the form of use of conversation in the film Lakar Pelangi by Andre Hirata there are some deviations principles of cooperation, 1) deviation maxim of quantity, 2) the deviation maxim of quality, 3) the deviation maxim of relevance, 4) deviation maxim way or implementation. A form of deviation principle of cooperation in the form of use of conversation in the film Lakar Pelangi by Andre Hirata there is some form of deviation principle of cooperation, the first deviation maxim of quantity, (a) speaker declared redundant information, (b) the speaker represents information that is not needed, the second deviation maxim of quality, (a) the speaker states the information that there is no evidence, (b) the speaker states the information unreasonable or illogical, third deviation maxim of relevance, speakers declared irrelevant information so that the impression hilarious, fourth deviation maxim implementation, (a) speakers stating the information vague that meaning was not clear, (b) the speaker states the information is ambiguous. (2) the implementation is the use of conversation in the film Lakar Pelangi by Andre Hirata as teaching materials politeness students in language learning in junior high school use language conversation polite, especially on VIII grade ie at SK 2. introduce yourself with simple sentences and language was polite, KD 5.1 introduce others degan right greeting sentence and the language santun. dan KD 5.2 greet others by using the right greeting sentence and polite language.